The Influence of Genre Theory on the Development of Contemporary Academic Texts - Simatupang, Dodi Satriawan; Ramadhan, Dio Fahry; Dika, Ewin Avriza; Hafiz, M. Rifqi (International Journal of Students Education, 2024)
This study aims to analyze the influence of genre theory on the development of contemporary academic texts through a literature review approach. By reviewing various sources and previous studies, this article identifies how understanding genre theory helps academic writers in composing texts that are in accordance with the expectations and conventions that apply in the academic community. This study shows that genre, as a social construction, provides important structural and functional guidance in academic writing. In addition, this study also reveals the challenges and opportunities faced by writers, especially those who use a second language, in understanding and applying the right genre in an academic context. The application of a genre-based approach in writing education has proven effective in improving the cohesion and coherence of academic texts. The findings also highlight the importance of innovation in academic genres, by using digital technology and multimodality elements that are increasingly relevant in scientific communication. Based on this literature review, it is recommended that genre-based approaches be strengthened in higher education curricula to support the development of more effective writing skills and in accordance with the demands of globalization of science